(untitled) (Journal of Engineering, 2024)
Battered piles are beneficial when used as foundations where significant lateral resistance is required, which could result from extreme water waves, winds, soil pressures, massive hits of explosions, or earthquakes. Experimental and numerical research must focus on that direction to reveal how these foundations behave under different loading conditions. The present study reviews the investigations conducted on the performance of batter pile foundations and attempts to understand and cover various aspects related to this issue; after conducting the review, the results indicate that the negative battered piles provide an efficient lateral stiffness corresponding to positive battered piles and a vertical one. Also, lateral bearing capacity improved with the inclusion of battered piles. Moreover, batter piles respond better than vertical piles in liquefiable soil under seismic excitation. The current study also showed that the pullout capacity of batter piles increased with the batter angle.